The role of technology extension and transfer in firms’ innovation and productivity in Peru - Ortiz, Miguel (2025)
This study examines how technology extension and transfer services (TETS) drive firm-level innovation and productivity. Since research and development (R&D) investments are subject to market failure, engaging with external agents enables firms to innovate at lower risk and cost. Using data from Peru’s National Innovation Survey (ENI), we apply the Crépon, Duguet, and Mairesse (CDM) model alongside propensity score matching (PSM) to enhance the reliability of our results. Additionally, we employ the generalized propensity score (GPS) method to analyze the sensitivity of innovation and sales outcomes to varying investment levels. The findings confirm that investment in training and external R&D significantly enhances innovation, thereby boosting labor productivity. However, this relationship is nonlinear, suggesting the presence of investment thresholds required to maximize impact.